Analysis of Government Needs and Strategies in the Provision of Hindu Religious Education Teachers: A Study of Education Policy in the Central Lombok Regency Government - I Made Intaran; I Wayan Agus Gunada (Jurnal Penelitian Agama Hindu, 2026)
Hindu religious learning in schools is highly dependent on the availability of adequate educators-likewise, implementing Hindu religious learning in schools in Central Lombok Regency. Hinduism is a minority, but the Central Lombok Regency Government has tried to provide Hindu teachers in schools. So, in-depth, the purpose of this study is to analyze and explore the needs and strategies of the government in providing Hindu educators in schools in Central Lombok Regency. The research used a qualitative method with a multisite case study approach in Central Lombok Regency. Interview and document analysis techniques are applied to collect data, and data is analyzed through reduction, data display, and data verification. Based on the findings on the research site, the need for Hindu religious educators in schools adjusts to the number of students. To get around the need for Hindu religious education teachers, the government got around it by combining Hindu students in several schools that were close in terms of domicile to the students. The government’s strategic step in providing Hindu teachers is through the submission of the formation of the selection of state civil servants to the Central Government and the distribution of teachers in schools so that the teaching load is evenly distributed. The findings explain that the Central Lombok Regency government is committed to providing decent access to education for all students, especially regarding religious harmony. This research is expected to be a literature study analyzing the needs of Hindu religious teachers in Indonesia and become a policy recommendation for relevant research in the future.